Evaluation of a mobile learning system to support correct medication use for health promotion - Ya-Ming Shiue; Yu-Chiung Hsu; Meng-Huei Sheng; Cheng-Hsuan Lan (International Journal of Management, Economics and Social Sciences (IJMESS), 2019)
Recently, the applications of mobile technology integration into innovative pedagogical approaches have resulted in new opportunities and challenges. The rapid development of mobile technology encourages student participation, knowledge sharing, collaboration, and the social interaction necessary to form authentic learning communities around student-generated content anytime and anywhere. Most health education interventions remain focused on traditional lecture methods and neglect the importance of student-centered learning approaches, few studies have examined the effectiveness of mobile technology on health promotion. Therefore, this paper designed a mobile learning system for learning correct medication use and investigated students' continuance usage intention. The findings revealed that students' satisfaction with mobile learning was the major factor predicting continuance intention.
Keywords: D83; I10; 330; Mobile learning system; mobile technology; expectation-confirmation model; continuance intention; correct medication use; health promotion